Research on the influence of the band edge processing on the process of linear flow splitting: Untersuchung des Einflusses der Blechkantenbearbeitung auf den Spaltprofilierprozess. Issue 1 (23rd December 2015) - Neuwirth, M.; Ahmels, L.; Schmidt, S.; Hegemann, M.; Groche, P.; Müller, C.
Abstract : Sheet metal is available in a wide range of properties and material composition. There are standardized quality characteristics for mechanical and geometrical properties in the plane of the sheet. However, the band edges are influenced by the correspondent metal working process and the properties may vary or be unknown. The forming zone of the manufacturing process linear flow splitting is located at the band edge. Thus, the knowledge of probable influences of metal working induced band edge properties on the process of linear flow splitting is essential and this knowledge will be presented in the following article.